3-Methyl-5-phenyl-1-(3-phenylisoquinolin-1-yl)-1H-pyrazole - Khan, F.N.; Manivel, P.; Kone, S.; Hathwar, V.R.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(25)H(19)N(3), is composed of an aryl-substituted pyrazole ring connected to an aryl-substituted isoquinoline ring system with a dihedral angle of 52.7 (1)degrees between the pyrazole ring and the isoquinoline ring system. The dihedral angle between the pyrazole ring and the phenyl ring attached to it is 27.4 (1)degrees and the dihedral angle between the isoquinoline ring system and the phenyl ring attached to it is 19.6 (1)degrees.